A narrative review on the role of traditional Chinese medicine (TCM) in treating coronary artery disease - Andong Zhang; Xiangpu Liu; Xuying Li; Na Duan; Bin Huang (Journal of the Pakistan Medical Association)
Coronary artery disease is one of the leading types of cardiovascular disorders globally, and is a significant contributor to mortality. Its prevalence is increasing annually, underscoring the need for innovative therapeutic strategies to enhance patient outcomes and quality of life. Despite the availability of numerous pharmacological treatments, there remains a critical need for novel interventions. Traditional Chinese medicine, with its centuries-old history, offers promising alternatives. The current narrative review was planned to examine 10 prominent Chinese herbal medicines currently in use, including Salvia miltiorrhiza, Hawthorn, Schisandra berry, Ginseng, Ginkgo biloba, Astragali radix, Reishi mushroom, Licorice root, Dang gui, and Cinnamon bark. While each of these traditional medicines holds potential for managing coronary artery disease, further large-scale clinical trials are warranted to draw more definitive conclusions.